Alocação de carbono e resposta oxidante em dois morfotipos de Paubrasilia echinata submetidos a diferentes condições de déficit de pressão de vapor e temperatura - Gasparini, Xismenia Soares da Silva (2019)
PPaubrasilia echinata is a tree species originating from the Atlantic Forest. This species has different morphotypes, among them the small and medium that differ in morphology and ecological habit. The small morphotype is described as an ombrophilous plant, while the medium morphotype shows heliophilic behavior. From the climate reports released, it is noted that environmental disturbances may occur as a result of these changes. According to reports, for the northeast portion of the Atlantic Forest is expected intense warming and reduction of rainfall. For the south / southeast portion, trends indicate warmer weather, with intensification in rainfall patterns. The objective of this study was to evaluate the combined effect of vapor pressure deficit (DPV) and temperature on carbon allocation, as well as non-enzymatic antioxidant responses (flavonoids, phenols and MDA) as mechanisms of tolerance to these climate changes. Therefore, plants of small and medium morphotypes were submitted to four different controlled environments (A), being A1- low DPV and temperature (0.7 KPa and 25.9 ° C); A2- low DPV and high temperature (31.6 ° C and 1.0 KPa); A3- high DPV and temperature (32.6 ° C and 3.1 KPa) and A4- high DPV and temperature (26 ° C and 1.7 KPa). The analysis of soluble sugars (AS), sucrose, reducing sugars (AR), starch and wall polymers (cellulose, hemicellulose and lignin) were performed in the three organs (leaf, stem and root) of plants of both morphotypes. Already the analyzes referring to the non- enzymatic oxidant system were performed in the leaves. Both morphotypes showed, in the A3 environment, higher concentration of leaf AS in relation to the stem and root. This result presented higher RA concentration and lower leaf sucrose concentration, since this carbohydrate can be used as osmoregulator, besides being the main translucent photoassimilate in plants and can be used in other reactions. The roots of the small morphotype, under elevated temperature, presented higher root concentration of sucrose compared to the other environments. In both morphotypes, the RA concentration was higher in leaves, especially in A3. Under high DPV, especially in A3, the small morphotype showed higher root starch concentration and lower leaf concentration. In the mean morphotype,. starch allocation was higher in leaves than in other organs. The highest starch concentration is related to storage organs (seeds, tubers, roots ...) and its lower leaf concentration is related to stress conditions. The high concentration of lignin in the roots of both morphotypes may favor water transport, besides protecting plant tissues from chemical / biological degradation. The highest concentration of cellulose and hemicellulose was observed in the medium morphotype A1 stems, and the opposite for the small morphotype. Regarding the oxidative reaction, the small morphotype presented higher content of H2O2 in A4, where the lipid peroxidation, indicated by the higher MDA content, was higher. The same result was observed for the average morphotype in A1. Under these conditions, the non enzymatic antioxidant system was inefficient due to the lower concentrations of phenols and flavonoids. In higher temperature environment, the small morphotype (A2) and the medium morphotype (A3) presented lower concentration of H2O2 and MDA. This result may suggest less cellular damage due to lower lipid peroxidation. Thus, it can be concluded that A1 and A4 appear to be stressful conditions for the small and medium morphotype, respectively. However A2 and A3 can be considered favorable environments, respectively, for the small and medium morphotypes.